2002
DOI: 10.1021/jf010794g
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Stilbene Oligomers and Astilbin in French Varietal Wines and in Grapes during Noble Rot Development

Abstract: Phenolics from grapes and wines can play a role against oxidation and development of atherosclerosis. Stilbenes have been shown to have cancer chemopreventive activity and to protect lipoproteins from oxidative damage. A method for the direct determination of stilbene oligomers (viniferin and pallidol) as well as astilbin in different types of wine using high-performance liquid chromatography with UV detection is described. In a survey of 21 commercial wines from the south of France, levels of pallidol and vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
3
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 30 publications
3
58
3
4
Order By: Relevance
“…red wine and the stage of noble rot development of the grapes, 15,16) these data suggest that both "-viniferin and resveratrol were key compounds preventing the pathogenesis of atherosclerosis and that "-viniferin may also be a strong candidate to explain the ''French paradox.'' Our data suggest that resveratrol activated Akt with subsequent accumulation of Nrf2 in the nucleus followed by HO-1 expression, thereby inhibiting the proliferation of VSMCs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…red wine and the stage of noble rot development of the grapes, 15,16) these data suggest that both "-viniferin and resveratrol were key compounds preventing the pathogenesis of atherosclerosis and that "-viniferin may also be a strong candidate to explain the ''French paradox.'' Our data suggest that resveratrol activated Akt with subsequent accumulation of Nrf2 in the nucleus followed by HO-1 expression, thereby inhibiting the proliferation of VSMCs.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to resveratrol, the functions of its oligomers, including "-viniferin, a dehydrodimer of resveratrol, have not yet been well investigated, although the "-viniferin content is comparable to or higher than that of resveratrol, depending on the type of red wine and the stage of noble rot development of the grapes; 15,16) "-viniferin is formed from resveratrol by oxidative processes. As examples, the red wine named Merlot 2000 contains 4.32 mg/L of "-viniferin and 3.04 mg/L of trans-resveratrol, while the red wine called Cabernet Sauvignon 2000 contains 1.23 mg/L of "-viniferin and an undetectable level of resveratrol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct insolation of berries increases soluble phenolics (Crippen and Morrison, 1986;Bergqvist et al, 2001). Biotic stress fosters the synthesis of resveratrol (Jeandet et al, 1995;Landrault et al, 2002). Deloire et al (2004) explain the relationship between stress, berry size and accumulation of anthocyanins.…”
Section: Terroir: Plant Physiological Aspectsmentioning
confidence: 99%
“…"-Viniferin content is comparable to or greater than resveratrol content, depending on the type of red wine and the stage of noble rot development of grapes. 11,12) Tran et al 13) indicated that "-viniferin has enhanced antioxidant activity as compared to resveratrol. Mi et al 14) demonstrated that "-viniferin was more potent than resveratrol in inducing the vasorelaxation of isolated thoracic aortas.…”
mentioning
confidence: 99%